Efektivitas Partisipasi Masyarakat dalam Pengelolaan Sampah Melalui Program Bank Sampah di Surabaya - Satya, Andiyasa Mahardhika; Pratiwi, Adellia Mega; Wardhana, Muhammad Fiqih Samudera (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Garbage has become a big problem and is an important issue in today’s urban environmental problems. The frequency of waste generation can never decrease or run out, even from time to time it increases along with the increasing growth of the human population and the complexity of human activities. The waste bank is a national program originating from the government, especially from the Ministry of Environment of the Republic of Indonesia. The definition of a Waste Bank according to the Regulation of the Minister of Environment of the Republic of Indonesia Number 13 of 2012 is a place for sorting and collecting waste that can be recycled and/or reused which has economic value. The research was conducted in 3 different places in the city of Surabaya, the first was the Samber Garbage Bank in Kec. Tegalsari, the second is the Pitoe waste bank in Jambangan, to be precise, RW 03 RT 07, and the third is the Surabaya Main Garbage Bank which is located in Pucang Sewu, Gubeng District. The variables studied include knowledge, attitudes, availability of sorting facilities, legality, regulation, sorting flow, source and final destination of waste, benefits of waste banks, community response (if there’s anything else, I’ll just remember that). The purpose of this research is to analyze the factors related to the effectiveness of community participation in the waste bank program that is already available in the city of Surabaya. The approach used in this research is qualitative. With the aim of knowing the effectiveness of community participation in waste management through the waste bank program in Surabaya.